Prevalence of various comorbidities among veterans with chronic kidney disease and its comparison with other datasets. (7th February 2016) - Patel, Nilang; Golzy, Mojgan; Nainani, Neha; Nader, Nader D.; Carter, Randolph L.; Lohr, James W.; Arora, Pradeep
Abstract: Chronic kidney disease (CKD) has a complicated interrelationship with various comorbidities. The purpose of this study was to describe the prevalence of various comorbidities among veterans with CKD and compare it with other datasets like Kidney Early Evaluation Program (KEEP), National Health and Nutrition Examination Survey (NHANES) and Medicare. Patients who had at least one outpatient visit in year 2007 (1 January 2007 to 31 December 2007) were included in the study ( n  =  75, 787). Glomerular filtration rate (eGFR) was estimated by the Modification of Diet in Renal Disease (MDRD) study equation. CKD prevalence was calculated based on one or two serum creatinine values at least 3 months apart. Demographic data were obtained including age, gender, race, weight, height and body mass index (BMI). The prevalence of various comorbidities was also collected based on ICD 9 codes from the problem list. The prevalence of CKD among veterans was 47.3%, much higher than estimated in the US population. Patients with CKD were more likely to have any vascular disease (36.89% vs. 14.87%), diabetes (34.18% vs. 17.83%), hypertension (86.65% vs. 57.56%), and cancer (18.69% vs. 9.23%). Irrespective of age, the prevalence of vascular disease was much higher among veterans with CKD. The prevalence of coronary artery disease, peripheral vascular disease, and cancer was much higher among elderly veterans with CKD as compared to other datasets. CKD is a growing endemic associated with a high frequency of concomitant chronic illnesses. Public health resources should be applied for early recognition and risk modification of CKD.